2005
DOI: 10.1080/00365520510023422
|View full text |Cite
|
Sign up to set email alerts
|

Small-bowel mucosal transglutaminase 2-specific IgA deposits in coeliac disease without villous atrophy: A prospective and randomized clinical study

Abstract: Clinically pertinent coeliac disease exists despite normal small-bowel mucosal villous architecture. Mucosal transglutaminase 2-specific IgA deposits can be utilized in detecting such patients with genetic gluten intolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 22 publications
1
110
2
Order By: Relevance
“…8 As a logical consequence, although there is a general consensus on dietary treatment for symptomatic subjects with enteropathy, it is not so for potential cases (i.e., patients with positive CDassociated serology, but no enteropathy). 9 However, accumulating evidence suggests that celiac patients may suffer from gluten-sensitive symptoms even before villous atrophy has developed, [10][11][12][13] and an increased risk of osteoporosis has been reported also for this group of patients. 10 In a recent work, Bertini et al have examined a cohort of CD patients, before and after gluten free diet GDF, and healthy controls, by 1 H NMR metabolic profiling of their serum and urine samples.…”
Section: Introductionmentioning
confidence: 99%
“…8 As a logical consequence, although there is a general consensus on dietary treatment for symptomatic subjects with enteropathy, it is not so for potential cases (i.e., patients with positive CDassociated serology, but no enteropathy). 9 However, accumulating evidence suggests that celiac patients may suffer from gluten-sensitive symptoms even before villous atrophy has developed, [10][11][12][13] and an increased risk of osteoporosis has been reported also for this group of patients. 10 In a recent work, Bertini et al have examined a cohort of CD patients, before and after gluten free diet GDF, and healthy controls, by 1 H NMR metabolic profiling of their serum and urine samples.…”
Section: Introductionmentioning
confidence: 99%
“…These deposits appear in the mucosa even before they are detectable in the periphery. 55,59,60 In IgA-deficient celiac disease patients, these mucosal autoantibody deposits appear in the IgM-class instead. 61 Autoantibodies associated with extraintestinal manifestations of celiac disease Interestingly, in some cases, autoantibodies against distinct selfmolecules in addition to TG2 have been reported to coincide with specific clinical manifestations of celiac disease.…”
Section: Intestinal Autoantibodiesmentioning
confidence: 99%
“…Notably, intestinal deposits of IgA antibodies targeting TG2 are present at all stages of CD, including early developing CD (Kaukinen et al, 2005) as well as late stage refractory CD (Salmi et al,2006) where patients may be seronegative. With regards to B cell activation and differentiation, the hapten carrier model proposed by Sollid et al (1997), although not formally demonstrated in vivo, appears to hold true, whereby gluten-specific T cells can provide help to TG-specific B cells.…”
Section: Pathogenesismentioning
confidence: 99%
“…Even patients with CD may not have gastrointestinal symptoms. In patients without overt gastrointestinal involvement (enteropathy), serum antibodies to TG2 may be absent (Kaukinen et al, 2005). Patients with extraintestinal manifestations typically 8 have antibodies primarily reacting with different TG isozymes, TG3 in DH and TG6 in patients with gluten ataxia (Sardy et al, 2002;.…”
Section: Diagnosis Of the Spectrum Of Gluten Related Diseasesmentioning
confidence: 99%